2017
DOI: 10.1177/2472555216687082
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Screening Model of the Tumor Microenvironment for Ovarian Cancer Cell Growth

Abstract: The tumor microenvironment plays an important role in the processes of tumor growth, metastasis and drug resistance. We have utilized a multilayered 3D primary cell culture model that reproduces the human ovarian cancer metastatic microenvironment to study the effect of the microenvironment on the pharmacological responses of cancer cells proliferation to different classes of drugs. A collection of oncology drugs was screened to identify compounds that inhibited the proliferation of ovarian cancer cells growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…are slightly earlier than day 11.625 for spheroid in silico (3). Their generation ratios with low activity must be greater than those for spheroid in silico (3) because the growth source index decreases earlier.…”
Section: Plos Onementioning
confidence: 83%
See 3 more Smart Citations
“…are slightly earlier than day 11.625 for spheroid in silico (3). Their generation ratios with low activity must be greater than those for spheroid in silico (3) because the growth source index decreases earlier.…”
Section: Plos Onementioning
confidence: 83%
“…Their generation ratios with low activity must be greater than those for spheroid in silico (3) because the growth source index decreases earlier. If the virtual inner proliferative activity is low up to the 13th generation, the ratios are 45.02% and 52.36% for in silico spheroids (1) and (2), respectively, which are slightly larger than the ratio of 41.17% for in silico spheroid (3). If the activity is low up to the 14th generation, both ratios are over 70%.…”
Section: Plos Onementioning
confidence: 88%
See 2 more Smart Citations
“…In the study of tumor progression as well as response to treatment, selection of the most appropriate model is essential since the composition of the in vitro system can strongly influence the result of the analysis. Recently, Lal-Nag et al (2017) compared the effects of different experimental models on ovarian cancer drug sensitivity. In particular, they developed a 3D model comprising ovarian cancer cells alone or co-cultured with the omentum metastatic niche, and they demonstrated that different microenvironments strongly influence response to treatment.…”
Section: In Vitro 3d Models Simulating Tumor Microenvironmenmentioning
confidence: 99%